Representation of radicalism in the series "bida'ah": a review of divine values in pancasila and its implications for students - Efendy, Defaria Eka Afizah; Yusuf, Nurbani; Wibowo, Arif Prasetyo (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
Radicalism is an ideology that demands drastic change, even violence, and in the context of religion, it is often manifested through intolerance and exclusivity. This research aims to examine the representation of radicalism in the series of Heresy, its relevance to the divine values of Pancasila and its implications for students. The method used is qualitative descriptive with content analysis, through non-participatory observation, literature review, and interviews. The results of the study show that radicalism is represented through narratives, dialogues, and visuals that depict the indoctrination and legitimacy of violence in the name of religion. The divine values of Pancasila function as a counter-narrative, emphasizing tolerance, moderation, and respect for diversity. Interviews with students reveal a critical awareness of the dangers of radicalism, although some consider the representation in the series to be stereotypical. These findings emphasize the importance of media literacy and religious literacy as civic education strategies to fight radicalism and strengthen students' national character